Influence of Dielectric Barrier Discharge treatment on Adhesion Properties of Platinum Coated Polypropylene Foil and Polypropylene Fabrics - Shahidi, S.; Wiener, J.; Ghoranneviss, M.; Štepánková, M. (Asian Journal of Chemistry, 2010)
This work report, the effects of low temperature plasma treatment on physical and chemical properties of polypropylene fabrics and foils. We have used a dielectric barrier discharge (DBD), working in an atmospheric pressure air. More polar functional groups were present on the substrate surface after dielectric barrier discharge pretreatment. The effects of plasma treatment on the adhesion properties of polypropylene samples were also studied. It is shown that the adhesion of fabrics and foils of polypropylene to platinum, when deposited on them, have been improved after plasma treatment.